Self‐management of musculoskeletal (MSK) conditions: What is most useful to patients? Protocol for a mixed methods systematic review. (2nd December 2021) - Wanless, Ben; Berry, Alice; Noblet, Tim
Abstract: Introduction: Musculoskeletal (MSK) conditions are the leading cause of disability in the United Kingdom, leading to ever‐growing waiting lists. Clinical guidelines highlight that most musculoskeletal conditions resolve in time and with little clinical input, and so supporting people to self‐manage is recommended to optimise healthcare resources. Despite this, the term self‐management remains ambiguous and to date no systematic review has evaluated if self‐management is a suitable, acceptable, and effective intervention/strategy for managing all MSK conditions. Methods and Analysis: This protocol is informed and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA). An advanced convergent qualitative meta‐integration mixed‐studies design will be used. Using a comprehensive predetermined search strategy, databases, key journals and grey literature will be searched independently by two reviewers. The reviewers will independently assess eligibility, complete data extraction, and evaluate for risk of bias using the Mixed Methods Appraisal Tool (MMAT). The overall quality of included studies will be evaluated using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) guidelines. Data from mixed‐methods studies will be transformed using a process of fractionation and analysed alongside the data extracted from the quantitative and qualitative studies, using descriptive analysis and thematic analysis, respectively. Ethics and dissemination: No research ethics are required for this systematic review since patient data will not be collected. The review will help to inform healthcare professionals and researchers on the most suitable, acceptable, and effective intervention/strategy for self‐managing MSK conditions. Results of this review will be submitted for publication in a peer‐reviewed journal and conference presentations.